Disinfectant Residual Provides Water Quality Information. Issue 10 (1st October 2013) - Martin, Barb; Ries, Tom
Abstract : The June 2013 Getting Optimized column (Distribution System Optimization Starts with Data) focused on identifying, collecting, and ensuring the accuracy of information required to enable data‐driven decisions to optimize distribution system performance. This month's column provides a more detailed look at data related to distribution system disinfectant residual and how it can be used as a water quality performance indicator.